Legal and Regulatory Aspects of Smart Contracts: A Systematic Review - Omar Farouk Al Mashhour; Ahmad Shamsul Abd Aziz; Nor Azlina Mohd Noor (Eurasian Journal of Management & Social Sciences, 2023)
As one of the fundamental technologies of blockchain, smart contracts have become one of popular and indispensable for certain businesses. Smart contracts have been introduced by Nick Szabo in 1997. However, the actual implementation was after the introduction of Blockchain, in particular, Ethereum. The enforceability of these contracts has always been dubious due to their unique characteristics and their considerable potential for abuse in criminal activities. The uncertainty stems mostly from these unique qualities and their connection to blockchain technology and cryptocurrencies. Consequently, determining the legal approach governing smart contracts is vital to ensuring the legal validity and the legal viability of such technology. This paper aims to provide a thorough overview and synthesis of prior literature on smart contracts and related regulatory implications (2016-2021). A thorough literature search of Scopus, Web of Science (WoS), Springer, and Emerald was done using two different combinations of key terms: “Smart Contracts AND Legality” and “Smart Legal Contracts AND Regulatory”. The final relevant articles were 22 articles found from 2016 to 2021. The narrowing of the literature search shows that smart contracts are a relatively new area that must be legally studied rather than merely focusing on the technical aspects. Ignoring the legal aspect would create uncertainly and inconsistency which might result in various legal dispute due to the nature of smart contracts. the novelty and lack of research represent one of the most major limitations of this research. However, it is crucial to highlight that the number of scientific journals published has increased significantly over the past five years, particularly in 2019 and 2020. This paper offers some guiding principles for academics, legal advisors, practitioners, and policymakers for their future research on smart contracts from a legal perspective.